Identification of work accommodations and interventions associated with work productivity in adults with migraine: A scoping review. (May 2021) - Begasse de Dhaem, Olivia; Gharedaghi, Mohammad Hadi; Bain, Paul; Hettie, Gabrielle; Loder, Elizabeth; Burch, Rebecca
Objective: To identify factors associated with work productivity in adults with migraine, and accommodations or interventions to improve productivity or the workplace environment for them. Methods: We conducted a scoping review by searching MEDLINE, Embase, PsycINFO, Cumulative Index of Nursing and Allied Heath Literature, and Web of Science from their inception to 14 October 2019 for studies of any design that assessed workplace productivity in adults with migraine. Results: We included 26 articles describing 24 studies after screening 4139 records. Five prospective cohort studies showed that education on managing migraine in the workplace was associated with an increase in productivity of 29-36%. Two studies showed that migraine education and management in the workplace were associated with increased productivity (absenteeism decreased by 50% in one study). One prospective cohort study showed that occupational health referrals were associated with more than 50% reduction in absenteeism. Autonomy, social support, and job satisfaction were positively associated with productivity, while quantitative demands, emotional demands, job instability, and non-conducive work environment triggers are negatively associated with productivity in workers with migraine. Conclusion: Despite migraine being the second leading cause of disability worldwide, there is a paucity of strong data on migraine-related work factors associated with productivity. Registration: None (scoping review)